Penerapan manajemen risiko dalam meminimalisir kredit bermasalah pada BPR Nusumma Jogja - Rahima, Annisa; Utami, Diah Dewi Rahmawati (Nur Science Institute, 2025)
This study aims to determine the implementation of credit risk management and the constraints faced at BPR Nusumma Jogja. This research uses a descriptive qualitative method with a phenomenological approach and discusses the application of credit management to minimize non-performing loans at BPR Nusumma Jogja. The results showed that the implementation of credit risk management at BPR Nusumma Jogja is carried out by identifying, measuring, monitoring, and controlling risks. There are obstacles during the implementation of credit risk management, including the lack of coordination between employees, credit officers who do not understand their duties, and lack of employee motivation. BPR Nusumma Jogja improves quality by separating the function between the Account Officer and the section that handles problem loans, socializing credit products to customers, a commitment by the BPR Nusumma Jogja credit team, and equipping all employees to be able to analyze credit problems.